Case Report: 56-year-old Woman Presenting with Progressive Hearing Loss, Chronic Otitis Media and Pulsatile Tinnitus - Luis Morejon-Troya; Joyce Jimenez-Zambrano (University Library System, University of Pittsburgh, 2019)
Introduction: Glomus tumors are rare benign lesions of the middle ear that are often associated with symptoms of progressive hearing loss and pulsatile tinnitus. Diagnosis is often delayed due to the slow growth of the tumor, and surgical resections of the mass are the mainstay treatment. Case Presentation: A 56-year-old Latin American female was admitted to the hospital with a year-long history of intermittent pulsatile buzzing noise, progressive hearing loss, pain and discharge of the left ear. High-resolution Computerized Tomography and Magnetic Resonance Imaging revealed evidence of an enhancing mass lesion, which extended into the external auditory canal. A tympanomastoidectomy was performed. Most of the mass was removed, but some remained because of massive bleeding. The patient received 3 months of radiation therapy after the tympanic paraganglioma was surgically removed. Conclusion: This case exposed the audiological findings, the location, and the extent of the tumor. Management options consist of radiation therapy and surgical management, depending on the size of the tumor. Early detection of glomus tumors is essential to prevent non-reversible complications.